2010
DOI: 10.1152/jn.00239.2010
|View full text |Cite
|
Sign up to set email alerts
|

Decoding and Cortical Source Localization for Intended Movement Direction With MEG

Abstract: Wang W, Sudre GP, Xu Y, Kass RE, Collinger JL, Degenhart AD, Bagic AI, Weber DJ. Decoding and cortical source localization for intended movement direction with MEG. J Neurophysiol 104: 2451-2461. First published August 25, 2010 doi:10.1152/jn.00239.2010. Magnetoencephalography (MEG) enables a noninvasive interface with the brain that is potentially capable of providing movement-related information similar to that obtained using more invasive neural recording techniques. Previous studies have shown that moveme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
45
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
2
2

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(52 citation statements)
references
References 66 publications
7
45
0
Order By: Relevance
“…J. Miller et al 2007;Wang et al 2009). In addition, Wang et al (Wang, Sudre, et al 2010) demonstrated that high-gamma band activity captured by MEG showed directional modulation similar to what was observed previously using invasive recordings in humans (ECoG) (Leuthardt et al 2004) and non-human primates (local field potentials) (Heldman et al 2006) and has been used for BMI control. Recently, Mellinger et al demonstrated that real-time MEG processing could provide control over a computer cursor in one-dimension with the individuals modulating their sensorimotor rhythms (mu and beta frequency bands) using imagined hand and feet movements (Mellinger et al 2007).…”
Section: Meg For Bmi Technology Research and Developmentsupporting
confidence: 69%
See 2 more Smart Citations
“…J. Miller et al 2007;Wang et al 2009). In addition, Wang et al (Wang, Sudre, et al 2010) demonstrated that high-gamma band activity captured by MEG showed directional modulation similar to what was observed previously using invasive recordings in humans (ECoG) (Leuthardt et al 2004) and non-human primates (local field potentials) (Heldman et al 2006) and has been used for BMI control. Recently, Mellinger et al demonstrated that real-time MEG processing could provide control over a computer cursor in one-dimension with the individuals modulating their sensorimotor rhythms (mu and beta frequency bands) using imagined hand and feet movements (Mellinger et al 2007).…”
Section: Meg For Bmi Technology Research and Developmentsupporting
confidence: 69%
“…It was also demonstrated that movement-related information could be decoded accurately from MEG signals (Georgopoulos et al 2005;Waldert et al 2008;Wang, Sudre, et al 2010). Figure 1 shows the time-frequency responses of a contralateral MEG sensor (a gradiometer) when a participant performed simple center-out wrist movements (Wang, Sudre, et al 2010). There is a clear decrease in power for the low frequency sensorimotor rhythm (10-30 Hz) and a distinct increase in power for the high-gamma band (60-200 Hz) during movement.…”
Section: Meg For Bmi Technology Research and Developmentmentioning
confidence: 95%
See 1 more Smart Citation
“…Several groups [2]- [4] showed that movement direction can be predicted during overt and imagined movements. Another group [5] decoded object category membership for animacy, naturalness, faces versus bodies or human versus nonhuman faces/bodies.…”
Section: Introductionmentioning
confidence: 99%
“…They used a stepwise LDA fed with data relative to the first 800 ms of the signal following the visual stimulations. Wang et al (2010) performed dimension reduction and MEG data transformation using an LDA that maximized linear discrimination among different movement directions.…”
Section: Introductionmentioning
confidence: 99%